Evaluation of intrathoracic tracheal narrowing in patients with obstructive ventilatory impairment using dynamic chest radiography: A preliminary study. Issue 129 (August 2020) - Watase, Sayaka; Sonoda, Akinaga; Matsutani, Noritsugu; Muraoka, Shintarou; Hanaoka, Jun; Nitta, Norihisa; Watanabe, Yoshiyuki
Highlights: Dynamic chest radiography can easily assess dynamic changes in tracheal diameter. Under forced expiration, obstructive ventilatory impairment narrows the trachea. Tracheal narrowing correlates with values of FEV1%-G, %V50, and %V25. Abstract: Purpose: Dynamic chest radiography (DCR) can observe the dynamic structure of the chest using continuous pulse fluoroscopy irradiation. However, its usefulness remains largely undetermined. The purpose of this study was to examine the relationship between changes in tracheal diameter during deep breathing and obstructive ventilation disorders using DCR. Method: Twelve participants with obstructive ventilatory impairment and 28 with normal pulmonary function underwent DCR during one cycle of deep inspiration and expiration. Three evaluators blinded to pulmonary function test results independently measured lateral diameters of the trachea in DCR images to determine whether there was a difference in the amount of change in tracheal diameter depending on the presence or absence of pulmonary dysfunction. Tracheal narrowing was defined as a decrease in the lateral tracheal diameter of more than 30 %. Participants were divided into a narrowing group and a non-narrowing group, and it was examined whether each group correlated with values of pulmonary function tests. Results: Tracheal diameter was significantly narrowed in subjects with obstructive ventilatory impairment compared to normal subjects ( P < 0.01). When subjects were divided into narrowing (tracheal narrowing rate [TNr] = 41.5 ± 7.7 %, n = 9) and non-narrowing groups (TNr = 9.1 ± 7.0 %, n = 31, p < 0.01), FEV1%-G, and %V25 were significantly smaller in the narrowing group than in the non-narrowing group ( p < 0.01). Conclusions: Changes in tracheal diameter during deep breathing were easily evaluated using DCR. DCR may, therefore, be useful for evaluating obstructive ventilation disorders.